Manifesto of the Communist Party from the Viewpoint of Social Responsibility - Mulej, Matijaž (Sociološki pregled, 2018)
In the light of Manifesto social responsibility is not only an informal promotion of systemic, i.e. requisitely holistic behavior, aimed at overcoming the current crisis and becoming a new socio-economic order, replacing the monopolistic neo-liberalism as soon as possible for humankind to survive and avoid the 3rd world war. It is also a tool of power-holders aimed at preventing the pending new socio-economic order and at keeping their privileges and benefts.
Keywords: systemic behavior; new socio-economic order; neo-liberalism; Social Responsibility; Manifesto of the Communist Party